Case Report: Hypergonadotropic hypogonadism in an elite athlete with variant in FSH receptor gene—clinical and sports implications of proper diagnosis - Skrzypiec-Spring, Monika; Zubkiewicz-Kucharska, Agnieszka; Pasińska, Magdalena; Rabijewski, Michał; Śmigiel, Robert; Szeląg, Adam (Frontiers in Endocrinology, 2025)
Hypergonadotropic hypogonadism is usually caused by the impairment of the structure and function of the gonads, but there are cases caused by reduced stimulation by the follicle-stimulating hormone (FSH) as a result of abnormal variants of genes encoding the follicle-stimulating hormone or its receptor (FSHR). We present the case of an elite athlete with the c.2039A>G variant in one allele of the FSHR gene resulting in hypergonadotropic hypogonadism, low testicular volume, and reduced semen parameters, placing particular emphasis on the diagnostic process and the importance of correct diagnosis in the context of possible treatment with gonadotropins, which can significantly improve fertility, increase testosterone levels, and, in the case of athletes, obtain approval from the anti-doping organization for treatment that increases testosterone levels.